Web-Based Motorcycle Spare Part Stock Management Information System at Geleng Classic Shop - Toti Fernanda Suprapto; Moh. Muhtarom; Bondan Wahyu Pamekas (International Journal Software Engineering and Computer Science (IJSECS), 2026)
Advances in information technology have encouraged businesses to adopt more effective inventory management systems. Geleng Classic Store still managed motorcycle spare part inventory manually using record books, resulting in recording errors, delays in updating information, inconsistencies between physical and recorded stock, and difficulties in monitoring inventory. These problems affected the efficiency of stock management and the availability of spare parts. This research aimed to design and develop a web-based inventory information system to support spare part stock management at a small and medium-sized enterprise. The system was developed using the waterfall model within the System Development Life Cycle (SDLC), consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the Laravel framework, PHP programming language, and MySQL database, with the First In, First Out (FIFO) method applied to inventory management. The developed system provides computerized recording of incoming and outgoing goods, real-time stock monitoring, minimum stock notifications, and role-based access according to user requirements. PIECES analysis indicated improvements in the management of performance, information, economics, control, efficiency, and service compared with the previous manual system. Black-box testing of ten main system features showed that all tested functions produced the expected results. The implementation of FIFO prioritizes older stock for release, supporting more orderly stock rotation and reducing the possibility of older items remaining in storage for extended periods. The developed system therefore provides a practical tool for supporting motorcycle spare part inventory management at Geleng Classic Store.